DISTINGUISHING NATURAL FROM SYNTHETIC AMETHYST: THE PRESENCE AND SHAPE OF THE 3595 CM-1 PEAK - Karampelas S.; Sklavounos S.; Fritsch E.; Zorba T.; Paraskevopoulos K.M. (My University, 2005)
The infrared absorption spectrum of amethyst in the region of stretching vibrations of X–OH groups reveals several bands that have been used for the separation of natural from synthetic amethyst. The intensity and shape of these bands have been measured as a function of crystallographic orientation. Using a resolution of 0.5 cm−1 the 3595 cm−1 band is present in all infrared spectra of natural amethyst and in some rare synthetic ones. If present in synthetic amethyst, its full width at half maximum (FWHM) is about 7 cm−1 whereas it is about 3 cm−1 in all natural samples. This new criterion, unlike the previous ones, seems appropriate to separate natural from synthetic amethyst in all cases.